The ‘Knowledge Region’ as a chance for newly conceptualizing guidelines for regional development - Fromhold-Eisebith, Martina (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
A growing number of regions in German speaking countries currently refer to the label of the ‘knowledge region’ in order to put into terms their strengths and development objectives. Besides the marketing value of the notion, however, ideas on which concrete substance may expediently fill this shell seem to be lacking. This paper calls for taking up the ‘knowledge region’ as a chance for newly reflecting on goals and approaches of regional development. The notion offers options to include tasks that have insufficiently been regarded before. The author suggests the heuristic concept of the ‘hexagon model of the knowledge region’, which captures a revised set of goals in structured ways with an applied perspective.